2006
DOI: 10.1101/lm.92706
|View full text |Cite
|
Sign up to set email alerts
|

The cerebellum in maintenance of a motor skill: A hierarchy of brain and spinal cord plasticity underlies H-reflex conditioning

Abstract: Operant conditioning of the H-reflex, the electrical analog of the spinal stretch reflex, is a simple model of skill acquisition and involves plasticity in the spinal cord. Previous work showed that the cerebellum is essential for down-conditioning the H-reflex. This study asks whether the cerebellum is also essential for maintaining down-conditioning. After rats decreased the soleus H-reflex over 50 d in response to the down-conditioning protocol, the cerebellar output nuclei dentate and interpositus (DIN) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 78 publications
(64 reference statements)
2
55
1
Order By: Relevance
“…As noted in the introduction, the changes in GABAergic function associated with operant conditioning of the H-reflex are part of a complex pattern of plasticity at spinal and supraspinal sites (see Wang et al 2006aWang et al , 2009Wolpaw and Chen 2006;Wolpaw 2010 for review). The effects of SMC stimulation may be similarly complex.…”
Section: Discussionmentioning
confidence: 99%
“…As noted in the introduction, the changes in GABAergic function associated with operant conditioning of the H-reflex are part of a complex pattern of plasticity at spinal and supraspinal sites (see Wang et al 2006aWang et al , 2009Wolpaw and Chen 2006;Wolpaw 2010 for review). The effects of SMC stimulation may be similarly complex.…”
Section: Discussionmentioning
confidence: 99%
“…In the first 24 h after the injections, exploratory behavior was attenuated. In subsequent days, they displayed postural and locomotor signs similar to those seen after cerebellar nuclear ablation in our previous studies Wolpaw and Chen 2006) (e.g., splaying of the back limbs, holding the trunk close to the ground, limb rigidity, intermittent hopping locomotion, occasional oscillatory head movements). These signs disappeared within 14 days.…”
Section: Methodsmentioning
confidence: 76%
“…All procedures were in accordance with the Guide for the Care and Use of Laboratory Animals (National Academy Press, 2011) and had been approved by the Institutional Animal Care and Use Committee of the Wadsworth Center. The protocols for implantation of the nervestimulating cuff and EMG recording electrodes, M-response and H-reflex elicitation, H-reflex conditioning, and data collection and analysis in freely moving rats have been fully described previously (Chen and Wolpaw 1995Wolpaw and Chen 2006;Wolpaw and Herchenroder 1990) and are reviewed here. The procedures for IO ablation and histological evaluation are described in detail below.…”
Section: Methodsmentioning
confidence: 99%
“…al, 2004;Zehr, 2006;Zehr et.al., 2007). Previous studies with the Hreflex demonstrated clearly that adaptive plasticity could be induced in the spinal cord and that it could be examined by using the H-reflex (Agaard, 2003;Carp & Wolpaw, 1994;Wolpaw & Chen, 2006). Some researchers have investigated the effectiveness of the Ia monosynaptic pathway in leg muscles in relation to the handedness.…”
Section: Neural Asymmetry Studies With the Use Of The Spinal Circuit mentioning
confidence: 99%